2013
DOI: 10.4238/2013.february.28.18
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of myostatin gene (MSTN) of Pekin duck and the association of its polymorphism with breast muscle traits

Abstract: Myostatin, encoded by the MSTN gene, is a negative regulator of muscle growth, and its expression level in muscle tissue is closely correlated with muscle growth and satellite cell proliferation. To identify the characteristics of the Pekin duck MSTN gene and the relationship between its polymorphism and breast muscle traits in Pekin duck, cDNA cloning and analysis and the expression pattern in breast muscle development and polymorphism were performed using molecular cloning, quantitative real-time reverse-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Furthermore, Xu et al . () studied polymorphisms in Pekin duck and identified three significant variations. The first is a c.129T>C subsitution located in the open reading frame and revealed an association with breast muscle thickness.…”
Section: Myostatin Polymorphisms In Poultrymentioning
confidence: 99%
“…Furthermore, Xu et al . () studied polymorphisms in Pekin duck and identified three significant variations. The first is a c.129T>C subsitution located in the open reading frame and revealed an association with breast muscle thickness.…”
Section: Myostatin Polymorphisms In Poultrymentioning
confidence: 99%
“…Five polymorphisms at the 5′ and 3′ promoter sites of the MSTN gene were shown to influence bone growth and fat metabolism [34]. In ducks of Pekin breed, the 129T>C polymorphism was associated with the thickness of the pectoral muscle [19]. In studies carried out by Zhong [20], 6 polymorphisms were…”
Section: Discussionmentioning
confidence: 99%
“…In ducks of Pekin breed, the 129T>C polymorphism was associated with the thickness of the pectoral muscle [19]. In studies carried out by Zhong [20], 6 polymorphisms were identified in the 3 exons of the MSTN gene in Sansui ducks, of which g.106>A was associated with slaughter traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSTN, ACB98643.1 MSTN cDNA was correctly obtained from P. fucata. As MSTN plays a pivotal role in muscle development, MSTN cDNAs have been cloned from representatives of several different vertebrate and invertebrate groups (Chen et al 2007;Ye et al 2007a;Covi et al 2008;Qian et al 2013;Xu et al 2013;Singh et al 2014). The results of previous studies clearly demonstrate several major differences in MSTN between these different groups.…”
Section: Discussionmentioning
confidence: 99%